Governance of knowledge and innovation in the Ibero-American agri-food system - Garcia-Alvarez-Coque, Jose-Maria; Saini, Eugenia; Esteban-Rodrigo, Esther; Mas-Verdu, Francisco (Spanish Journal of Agricultural Research, 2020)
Aim of study: Governance and the knowledge and innovation system (KIS) are interrelated concepts. Knowledge management best practices are linked to KIS performance. This article explores the governance of the leading research, development, and innovation institutes in Ibero-American agriculture, food, and agro-industry sector. The paper reports mapping of the governance of 20 agricultural research institutes.Area of study: Latin America and the Caribbean, Spain and Portugal.Material and methods: In total, 51 strategic objectives for effective governance were identified. Self-evaluation by the National Agricultural Research Institutes (NARIs) was validated at a workshop backed by FONTAGRO, a cooperation mechanism amongst Latin American and the Caribbean countries, Portugal and Spain, and the Ibero-American Network of NARIs.Main results: As a strength, the key dimension of NARIs appears to be coordination and cooperation. This result was acknowledged in the internal and external evaluations and supports previous research on the relevance of innovation networks in Latin America. By contrast, as a challenge, the key dimension appears to be demand articulation, followed closely by capacity building. Most of the institutes are also well-positioned to develop deeper ties with social and environmental challenges.Research highlights: In the medium and long term, NARIs should make efforts to improve the processes of organizational evaluation and learning, demand articulation, and strategic direction of the institutions. Improvement in management processes, in addition to best practices for social responsibility and gender equality, appear to be short-term priorities.